Defining reasonable patient standard and preference for shared decision making among patients undergoing anaesthesia in Singapore. Issue 1 (December 2017) - Yek, J.L.J.; Lee, A.K.Y.; Tan, J.A.D.; Lin, G.Y.; Thamotharampillai, T.; Abdullah, H.R.
Abstract Background A cross-sectional study to ascertain what the Singapore population would regard as material risk in the anaesthesia consent-taking process and identify demographic factors that predict patient preferences in medical decision-making to tailor a more patient-centered informed consent. Methods A survey was performed involving patients 21 years old and above who attended the pre-operative evaluation clinic over a 1-month period in Singapore General Hospital. Questionnaires were administered to assess patients' perception of material risks, by trained interviewers. Patients' demographics were obtained. Mann–WhitneyU test and Kruskal-Wallis one-way analysis of variance was used. Statistical significance was taken atp  < 0.05. Results Four hundred fourteen patients were eligible of which 26 refused to participate and 24 were excluded due to language barrier. 364 patients were recruited. A higher level of education (p  < 0.007), being employed (p  < 0.046) and younger age group (p  < 0.003) are factors identified in patients who wanted greater participation in medical decisions. Gender, marital status, type of surgery, and previous surgical history did not affect their level of participation. The complications most patients knew about were Nausea (64.8%), Drowsiness (62.4%) and Surgical Wound Pain (58.8%). Patients ranked Heart Attack (59.3%), Death (53.8%) and Stroke (52.7%) as the most significant risks that they wanted to be informed about in greater detail. Most patients wanted to make a joint decision with the anaesthetist (52.2%), instead of letting the doctor decide (37.1%) or deciding for themselves (10.7%). Discussion with the anaesthetist (61.3%) is the preferred medium of communication compared to reading a pamphlet (23.4%) or watching a video (15.4%). Conclusion Age and educational level can influence medical decision-making. Despite the digital age, most patients still prefer a clinic consult instead of audio-visual multimedia for pre-operative anaesthetic counselling. The local population appears to place greater importance on rare but serious complications compared to common complications. This illustrates the need to contextualize information provided during informed consent to strengthen the doctor-patient relationship.